The value of phenylalanine in predicting atrial fibrillation risk in chronic heart failure - Zhou, Qing-Fen; Lu, Qiu-Ya; Dai, Yang; Chen, Qiu-Jing; He, Xiao-Shuang; Chen, Shuai; Zhao, Jun-Tao; Zhang, Feng-Ru; Lu, Lin; Yang, Fan (Frontiers in Cardiovascular Medicine, 2024)
Backgrounds Atrial fibrillation (AF) is a common complication of chronic heart failure (HF). Serum phenylalanine (Phe) levels are related to inflammation disorder. It is meaningful to study the circulating Phe with AF occurrence in HF. Methods The cross-sectional study recruited 300 patients (78.0% male; mean age, 65 ± 13 years) with HF (left ventricular ejection fraction of ≤50%, containing 70 AF patients) and 100 normal controls. Serum Phe value was measured by liquid chromatography–tandem mass spectrometry. Logistic regression analysis was conducted to measure the association between Phe and AF risk in HF. The association between Phe and high-sensitivity C-reactive protein (hsCRP) was assessed by simple correlation analysis. In the prospective study, the 274 HF subjects (76.6% male; mean age, 65 ± 13 years) were followed up for a mean year (10.99 ± 3.00 months). Results Serum Phe levels increased across the control, the HF without AF, and the HF with AF groups (77.60 ± 8.67 umol/L vs. 95.24 ± 28.58 umol/L vs. 102.90 ± 30.43 umol/L, ANOVA P < 0.001). Serum Phe value was the independent risk factor for predicting AF in HF [odds ratio (OR), 1.640; 95% CI: 1.150–2.339; P = 0.006]. Phe levels were correlated positively with hsCRP value in HF patients with AF (r = 0.577, P < 0.001). The elevated Phe levels were associated with a higher risk of HF endpoint events in HF patients with AF (log-rank P = 0.005). Conclusions In HF with AF subjects, elevated Phe value confers an increased risk for prediction AF and was more related to poor HF endpoint events. Phe can be a valuable index of AF in HF.